The Relationship Of Nutritional Status With The Incidence Of Metabolic Syndrome In Security And Order Employees In Universitas Pendidikan Indonesia - Putri, Mutiara Meidina; Nurhalimah, Ananda Salma; Anindya, Intan Divany; Rifaldi, Mochamad Sidiq; Azzahra, Salma Tria (Journal of Applied Food and Nutrition, 2024)
Background: Metabolic syndrome is a real threat to the occurrence of non-communicable diseases. One of the factors that causes metabolic syndrome is a person's nutritional status. Survey results state that the increasing incidence of metabolic syndrome is related to changes in his, her, their, etc. lifestyle, namely changes in physical activity, lack of exercise and changes in consumption patterns. Unbalanced calorie intake and usage results in excess nutritional status (obesity). Based on this, this research aims to determine the relationship between nutritional status and the incidence of metabolic syndrome in UPI K3 employees.Research Methods: The design used is cross sectional. The population is K3 employees of the University of Education, Indonesia. The research sample was taken using a purposive sampling method from 30 K3 officers at the Indonesian University of Education, Bandung City. Data processing uses the chi-square correlation test.Research Result: The results of the study showed that there was a significant relationship between nutritional status and the incidence of metabolic syndrome with a p value = 0.029 (0.05). A person with an obese nutritional status has a 5.091 times greater risk of experiencing metabolic syndrome than a person who has a normal nutritional status or is thin. This is because obese sufferers have a greater risk of developing other complications.Conclusion: there is a significant relationship between nutritional status and the incidence of metabolic syndrome. The importance of implementing a healthy lifestyle, especially in managing adequate diet and exercise to reduce the incidence of metabolic syndrome.